Scoping review protocol of the use of eye movement desensitisation and reprocessing in the treatment of birth trauma - Laura Ward; Susan O’Donovan; Ruth Melia (BMJ Open)
Introduction A traumatic childbirth can have severe negative effects on the mental health of the mother and can negatively impact the child and partner. Eye movement desensitisation and reprocessing (EMDR) is a psychological intervention used to treat symptoms of trauma. The National Institute for Health and Care Excellence guidelines for antenatal and postnatal mental health recommend that trauma-focused cognitive behavioural therapy or EMDR should be offered to women who suffer from post-traumatic stress disorder resulting from a traumatic birth. However, the use of EMDR for birth trauma has not been clearly outlined in the literature.Objectives The aim of this scoping review is to explore the extent of the currently available research and to identify knowledge gaps in the use of EMDR for treating birth trauma.Methods and analysis The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines will be followed to provide a comprehensive scoping review of the use of EMDR for birth trauma. Several databases will be searched, such as PsychInfo, Pubmed, the Cochrane Library, Embase, Scopus and CINAHL, from the date the database was developed, until approximately August 2026. The grey literature sources will also be searched, and searches will be limited to include studies written in the English language. Two researchers will independently screen and extract data from both quantitative and qualitative studies, which meet the inclusion criteria. Data will be analysed in a descriptive and thematic manner. Data extraction may include study characteristics, data collection procedures, outcomes and results. Findings will be presented in tabular and narrative formats.Ethics and dissemination Ethical Approval is not necessary for this review, as only secondary data will be used. It is expected that the review will be disseminated at psychological conferences and in relevant journal articles.Trial registration number This scoping review protocol has been registered on Open Science Framework. The registration DOI is: https://doi.org/10.17605/OSF.IO/UJZ52.